2006
DOI: 10.1097/hjh.0b013e328010918b
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring in obese children: role of insulin resistance

Abstract: The results of the present study indicate that adiposity and insulin resistance have an important role in influencing blood pressure in obese children, and also show a high prevalence of non-dipping phenomenon. This is of particular relevance because blood pressure tracks from childhood into adulthood and an already early-life high blood pressure is associated with an increased cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
6
34
2
5
Order By: Relevance
“…It has been shown that overweight, obesity and generally increased visceral accumulation are closely related to increased office SBP (but not DBP) in children, 10,28,29 whereas other studies have indicated that obesity is related with both increased office SBP and DBP. 7,8,30 The present results showed that obesity might explain in greater extent the variability of SBP (both at home and in the office) than that of DBP (r 2 0.092 and 0.122 for office and home SBP vs 0.055 and 0.056 for DBP, respectively; Table 2). However, a major discrepancy was that BMI (z-score) was a more important determinant of home than office SBP.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It has been shown that overweight, obesity and generally increased visceral accumulation are closely related to increased office SBP (but not DBP) in children, 10,28,29 whereas other studies have indicated that obesity is related with both increased office SBP and DBP. 7,8,30 The present results showed that obesity might explain in greater extent the variability of SBP (both at home and in the office) than that of DBP (r 2 0.092 and 0.122 for office and home SBP vs 0.055 and 0.056 for DBP, respectively; Table 2). However, a major discrepancy was that BMI (z-score) was a more important determinant of home than office SBP.…”
Section: Discussionsupporting
confidence: 49%
“…6 Conflicting data exist regarding the possible predominant effects of weight gain on office systolic blood pressure (SBP) rather than diastolic blood pressure (DBP) in children and adolescents. Some studies suggested that excessive body weight causes a comparative elevation in both SBP and DBP, [7][8][9] whereas others showed that weight gain increases SBP more than DBP. 10,11 Moreover, studies in children and adolescents consistently showed a higher prevalence of systolic rather than diastolic hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance in obesity is strictly related to the development of hypertension (36,37), dyslipidemia (38), IGT (39), hepatic steatosis (40), as well as to the combination of these factors, also known as metabolic syndrome (41). Furthermore, insulin resistance is associated with systemic inflammation, endothelial dysfunction, early atherosclerosis and disordered fibrinolysis (42) (Fig.…”
Section: Insulin Resistance and Associated Complicationsmentioning
confidence: 99%
“…Central adiposity and insulin resistance have been indicated as determinants of blood pressure levels in childhood. 5 Hypertension is an important risk factor for cardiovascular diseases, which represent one of the principal causes of mortality and morbidity worldwide. 6 Because of the potential for serious complications, hypertension has become a major public health problem.…”
Section: Introductionmentioning
confidence: 99%